2007
DOI: 10.1093/ageing/afm005
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of Tai Chi and resistance exercise on bone health, muscle strength and balance in community-living elderly people

Abstract: The beneficial effects of TC or RTE on musculoskeletal health are modest and may not translate into better clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
295
4
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(323 citation statements)
references
References 27 publications
6
295
4
14
Order By: Relevance
“…The review included three studies which examined Tai Chi and its effect in older adults specifically [88][89][90], but all were found only to be of moderate methodological quality. Amongst healthy but sedentary older adults Tai Chi was found to stimulate bone metabolism significantly more than resistance training [90].…”
Section: Bone Density and Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…The review included three studies which examined Tai Chi and its effect in older adults specifically [88][89][90], but all were found only to be of moderate methodological quality. Amongst healthy but sedentary older adults Tai Chi was found to stimulate bone metabolism significantly more than resistance training [90].…”
Section: Bone Density and Osteoporosismentioning
confidence: 99%
“…Although, in frail institutionalised older adults it was found to increase bone density and reduce fracture rate [88]. Nonetheless, the studies included in the Lee et al [87] review measured bone mineral density in different ways, such as BMD [88,89] or bone metabolism [90] and therefore it is difficult to make direct comparisons between studies, with no further studies identified.…”
Section: Bone Density and Osteoporosismentioning
confidence: 99%
“…Two of these were considered well designed, and they both reported significant differences in psychological and physiological symptoms when compared with a psychosocial sup-port control. 104 Hence, data to support the use of tai chi is encouraging but limited and inconclusive.…”
Section: Tai Chimentioning
confidence: 99%
“…Mesmo os autores que não encontraram evidências da eficácia do TCC na estabilidade postural, 16 no equilíbrio, na RA e na força, 17 reconhecem que há diminuição na incidência de quedas e no medo de cair nos idosos praticantes dessa modalidade de exercício. Embora Logghe et al 18 argumentem que a melhora da CF com a prática do TCC aplica-se somente aos idosos frá-geis institucionalizados, nossos achados não são concordantes com essa afirmação.…”
Section: Capacidade Funcionalunclassified